X-Ray fluorescence (XRF) of discrete samples from IODP Hole 386-M0086B - Michael Strasser; Ken Ikehara; Jeremy D Everest; Lena Maeda; Katharina Hochmuth; Hannah Grant; Margaret S Stewart; Noriaki Sakurai; Takahiro Yokoyama; Rui Bao; Piero Bellanova; Morgane Brunet; et al. (PANGAEA, 2025)
Results of X-Ray fluorescence (XRF) on discrete samples from the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). The offshore phase of this expedition took place between 2021-04-13 and 2021-06-01 onboard Japanese R/V Kaimei from and to Yokosuka, Japan, followed by an onshore phase onboard D/V Chikyu between 2022-02-14 – 2022-03-15. During the onshore phase a set of solid-phase samples, with a volume of approx. 10 cubic centimeters each, were taken with the purpose to be later on split into aliquots for the following three analyses: X-ray diffraction, carbon and X-ray fluorescence. The bulk solid-phase samples were taken from the work halves of core sections at about one sample per meter on average. Unprocessed samples were then shipped to the MARUM - Center for Marine Environmental Sciences of the University of Bremen (Germany), where they were freeze-dried, ground and homogenized to a fine powder by ECORD Science Operator staff using a pestle and an agate mortar. For analysis of elemental composition of the bulk sediment using energy dispersive XRF (EDXRF) 4 g (±0.2 g) aliquot of the homogenized powder was used. Elemental concentrations were determined by ED-XRF spectroscopy utilizing a PANalytical Epsilon 3-XLE benchtop ED-XRF spectrometer operated in the MARUM sediment geochemistry laboratory. For further details see methods chapter in0.167emStrasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023